A multicentre audit of HDR/PDR brachytherapy absolute dosimetry in association with the INTERLACE trial (NCT015662405). (9th November 2017) - Díez, P; Aird, E G A; Sander, T; Gouldstone, C A; Sharpe, P H G; Lee, C D; Lowe, G; Thomas, R A S; Simnor, T; Bownes, P; Bidmead, M; Gandon, L; et al.
Abstract: A UK multicentre audit to evaluate HDR and PDR brachytherapy has been performed using alanine absolute dosimetry. This is the first national UK audit performing an absolute dose measurement at a clinically relevant distance (20 mm) from the source. It was performed in both INTERLACE (a phase III multicentre trial in cervical cancer) and non-INTERLACE brachytherapy centres treating gynaecological tumours. Forty-seven UK centres (including the National Physical Laboratory) were visited. A simulated line source was generated within each centre's treatment planning system and dwell times calculated to deliver 10 Gy at 20 mm from the midpoint of the central dwell (representative of Point A of the Manchester system). The line source was delivered in a water-equivalent plastic phantom (Barts Solid Water) encased in blocks of PMMA (polymethyl methacrylate) and charge measured with an ion chamber at 3 positions (120° apart, 20 mm from the source). Absorbed dose was then measured with alanine at the same positions and averaged to reduce source positional uncertainties. Charge was also measured at 50 mm from the source (representative of Point B of the Manchester system). Source types included 46 HDR and PDR 192 Ir sources, (7 Flexisource, 24 mHDR-v2, 12 GammaMed HDR Plus, 2 GammaMed PDR Plus, 1 VS2000) and 1 HDR 60 Co source, (Co0.A86). Alanine measurements when compared to the centres' calculated dose showed a mean difference (±SD) of  +1.1% (±1.4%) at 20 mm. Differences were also observed between source types and dose calculation algorithm. Ion chamber measurements demonstrated significant discrepancies between the three holes mainly due to positional variation of the source within the catheter (0.4%–4.9% maximum difference between two holes). This comprehensive audit of absolute dose to water from a simulated line source showed all centres could deliver the prescribed dose to within 5% maximum difference between measurement and calculation.